Potencial fertilizante do lodo de esgoto para o cultivo de trigo, antes e após sua biotransformação - Torres Riveros, Israel César Andrés (2024)
Brazil is one of the largest agricultural producers in the world and the fourth largest consumer of fertilizers. The country consumes around 8% of the world's total fertilizers, with more than 70% of this volume being imported. In this sense, the use of Sewage Sludge (SS), a by-product of Sewage Treatment Plants (STP), as organic fertilizer has been proposed. This fact is justified because this waste contains a high amount of organic matter, macronutrients and micronutrients, favoring plant growth, in addition to providing an environmentally and economically more sustainable solution for its disposal. For this reason, the present work aimed to evaluate the use of SS as an organic fertilizer for wheat cultivation, before and after biotransformation by biostimulation processes with rice husk (RH) and/or bioaugmentation with the fungus Pleurotus ostreatus (PL). The biotransformation of LE was carried out by arranging the SS samples; SS+ soil (S), SS+ S + RH; SS + S + PL; and SS + S + RH + PL; in stainless steel vats, stored in a covered place at room temperature, for a period of 3 months. Subsequently, the samples were evaluated for their phytotoxicity through tests with lettuce seeds and their application as organic fertilizer at a dose of 40 t.ha-1 based on greenhouse experiments on wheat crops. In the acute toxicity test with lettuce, the SS samples were found to be highly toxic. However, when mixed with soil at a dose of 40 t.ha-1, the treatments were moderately toxic, with values ranging from 40 to 80% on the germination index. The results obtained from the application of SS (biotransformed or in natura) as an organic fertilizer indicate that this material contributed significantly to the growth, development, productivity and concentration of macronutrients within the wheat plant. Furthermore, the treatments presented amounts of heavy metals in the grains below the permitted concentration limits, making them safe for sale and consumption. No toxic effect was observed on the wheat plants grown under these treatments. Only a slight reduction in root length and dry matter was noted, with the SS in natura showing the greatest reduction at 1.5 g compared to the soil. Although all treatments boosted wheat development significantly more when compared to soil with mineral fertilizer, Principal Component Analysis (PCA) identified the SS treatment biotransformed by biostimulation (SS+S+RH) as the most advantageous, standing out with 31 leaves per plant, a stem diameter of 5.64 mm, and a root length of 469 m. This was followed by SS+S+RH+PL, which excelled in root dry matter, showing an increase of 1.1 g compared to the soil. This fact demonstrated that the biostimulation process with RH was more effective in terms of its agronomic potential. Thus, the use of SS as an organic fertilizer for wheat can represent an interesting option, as in addition to reducing production costs related to the use of imported fertilizers, a more sustainable destination is given to the SS, also reducing the costs generated with the destination of this waste and, consequently, reducing the problems it can generate for the environment.